2017
DOI: 10.1177/0030222817725181
|View full text |Cite|
|
Sign up to set email alerts
|

Mothers Coping With Bereavement in the 2008 China Earthquake: A Dual Process Model Analysis

Abstract: The purpose of this study is to explore the grief experiences of mothers after they lost their children in the 2008 China earthquake. Informed by the dual process model, this study conducted in-depth interviews to explore how six bereaved mothers coped with such grief over a 2-year period. Right after the earthquake, these mothers suffered from intensive grief. They primarily coped with loss-oriented stressors. As time passed, these mothers began to focus on restoration-oriented stressors to face changes in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Strobe & Schut (1999) [22] 1. loss-oriented coping 2. restoration-oriented coping this model focused on the two coping strategies for stressors related to grief the mourners recover from grief by oscillating between the two coping strategies in daily life some studies have attempted to validate this model. Chen et al [26] supported the importance of this model in their study on disaster survivors rstb.royalsocietypublishing.org Phil. Trans.…”
Section: Normal Grief and The Mourning Processmentioning
confidence: 84%
See 2 more Smart Citations
“…Strobe & Schut (1999) [22] 1. loss-oriented coping 2. restoration-oriented coping this model focused on the two coping strategies for stressors related to grief the mourners recover from grief by oscillating between the two coping strategies in daily life some studies have attempted to validate this model. Chen et al [26] supported the importance of this model in their study on disaster survivors rstb.royalsocietypublishing.org Phil. Trans.…”
Section: Normal Grief and The Mourning Processmentioning
confidence: 84%
“…Therefore, the bereaved lower their distress levels through adaptive avoidance, similar to protective exclusion and reappraisal of the meaning of death, while oscillating between avoidance and confrontation. Validity of the dual model process in different contexts with various types of bereavement has been addressed in several studies [26,31,32]. Chen et al [26] reported that six mothers who lost their children in the 2008 China earthquake primarily coped with loss-oriented stressors and shifted their focus to restoration-oriented stressors to deal with the situation over time.…”
Section: Normal Grief and The Mourning Processmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, emotional help and care from family members, friends, and neighbours can alleviate depressive symptoms, especially in rural China, where the relationship between neighbours may be closer than that of distant relatives (Fan et al, 2018). More evidence-based grief work with a focus on the Dual Process Theory (Stroebe & Schut, 2010), meaning-making (Neimeyer, Klass, & Dennis, 2014), and increased awareness of the challenges of disenfranchised grief (Doka, 2002) are needed to help Shidu parents adapt to the changes in their lives and establish new meaning (Chen, Fu, Sha, Chan, & Chow, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the first stage of severe grief, a good spousal relationship was a protective factor for intensive loneliness. Couples’ dyadic coping (constructive communication, emotion sharing, and joint problem-solving) was critical when they felt stigmatized and reluctant to socialize or receive external support (Bergstraesser et al, 2015; L. Chen, Fu, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%